Romiplostim as a treatment for immune thrombocytopenia: a review - Chalmers, Sarah (J Blood Med, 2015)
“Immune thrombocytopenia” (ITP) is an autoimmune disorder that leads to peripheral destruction, as well as a decreased production of platelets. ITP most commonly presents as mild mucocutaneous bleeding. Though it is rare, the leading cause of mortality in persons with ITP is intracranial hemorrhage and those that do not respond to therapy are at increased risk. Our understanding of the pathophysiology of ITP has evolved immensely, especially over the last 60 years. The discovery of the platelet-production stimulator, thrombopoietin (TPO), lent clarity to an earlier hypothesis that inhibition of platelet production at the level of the megakaryocyte, at least in part, accounts for thrombocytopenia in adults with ITP. This facilitated the development of TPO-based therapies to treat ITP. Thrombopoietin receptor agonists are one of the most recent treatments to enter the landscape. Original production of a recombinant human TPO was halted after clinical trials revealed the untoward effect of autoantibodies to the recombinant human TPO with cross-reactivity to endogenous TPO. Next-step development focused on stimulation of the TPO receptor with fewer immunogenic agents. Currently, two such thrombopoietin receptor agonists, romiplostim and eltrombopag, are licensed in the USA to treat thrombocytopenia in adults with persistent or chronic ITP. Ongoing research will assess their efficacy in other immune-mediated and nonimmune-mediated primary and secondary thrombocytopenias.